Ordinance no. 29, An Ordinance to Preserve the Public Peace § 1, in Revised Charter of the City of Ypsilanti (1898) (Approved 1882). - (:unkn) unknown (My University, 1882)
Prohibited the concealed carry of firearms, dirks and other deadly weapons
Keywords: CARRY - CONCEALED